The effect of poly(D,L-lactide) modification with poli[(R,S)-3-hydroxybutyrate] on the course of its degradation in natural environments - Krasowska, K.; Brzeska, J.; Rutkowska, M.; Dacko, P.; Sobota, M.; Kowalczuk, M. (Polimery, 2022)
The results of environmental degradation of poly(D,L-lactide) (PLA), unmodified or modified with amorphous poly[(R,S)-3-hydroxybutyrate] (a-PHB), in the compost pile with activated sludge or in the Baltic Sea water were presented. The changes of characteristic parameters of both these environments were monitored during the degradation process (Table 1 and 2). The processes of samples degradation in the applied natural conditions were characterized by macroscopic surfaces’ changes (Fig. 1) as well as by changes of samples weights (Table 3), molecular weights (Fig. 2) and mixtures compositions (Table 4). It was found that PLA degradation rate depended both on environment type and its conditions. Namely, degradation process is faster in the compost than in sea water. The presence of a-PHB accelerates the degradation process and the greater modifier content the faster degradation (Fig. 3). It was stated that PLA degradation in the natural environments results from both enzymatic hydrolysis and chemical hydrolysis of ester bonds. In sea water environment the chemical hydrolysis runs while in the compost both mechanisms act with predominant role of enzymatic one.